Complex odontoma and the use of platelet-rich fibrin for wound healing - Roshanghias, Korosh; Sophie Gharaei; Julia Gharaei; Andre Peisker (Journal of Orofacial Research, 2023)
Complex odontomas are asymptomatic, benign odontogenic growths, more prevalent in the male and pediatric population. Although often found incidentally on radiography as a radio-dense mass, surgical removal is often necessary to prevent future complications. The use of autologous platelet-rich fibrin (PRF) has been shown to aid in wound healing and post-operative recovery. Here, we report the case of a 30-year-old male presented with a left mandibular mass on radiography. Intraoral examination revealed an asymptomatic swelling, identified as a complex odontoma by histopathology after removal. Complete excision was undertaken by piezosurgery, and the addition of PRF resulted in excellent recovery.